2022
DOI: 10.3390/nu14040725
|View full text |Cite
|
Sign up to set email alerts
|

Reply to von Bünau et al. Comment on “Depoorter, L.; Vandenplas, Y. Probiotics in Pediatrics. A Review and Practical Guide. Nutrients 2021, 13, 2176”

Abstract: We agree with Prof. Stange and Erhardt for their comment on our paper on Probiotics in Pediatrics [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Before changing diets to improve nutrient composition, it is crucial to determine the dietary intake of the target population. Studies have found that rural people consume large amounts of protein and carbohydrate-containing foods, while most respondents' diets do not contain sufficient dietary fiber [ 45 ]. Although protein intake was high, it was mainly of plant rather than animal origin.…”
Section: Key Fields and Hot Topicsmentioning
confidence: 99%
“…Before changing diets to improve nutrient composition, it is crucial to determine the dietary intake of the target population. Studies have found that rural people consume large amounts of protein and carbohydrate-containing foods, while most respondents' diets do not contain sufficient dietary fiber [ 45 ]. Although protein intake was high, it was mainly of plant rather than animal origin.…”
Section: Key Fields and Hot Topicsmentioning
confidence: 99%